APPLYING GENERIC STRATEGY IN CREATING CUSTOMER LOYALTY IN THE MIDDLE OF PANDEMI VIRUS COVID-19 IN POLYCLINIC MCU XYZ CARDIOVASCULAR HOSPITAL - Mastari, Mastari (Dinasti International Journal of Management Science, 2020)
Background this study is to find the importance of the application of strategy generic consisting of the strategy differentiation, strategy cost leadership and strategies focus on created customer loyalty in the centre of the condition pandemics an outbreak of the disease covid-19 in polyclinic MCU XYZ Cardiovascular Hospital in determine policy in order to anticipate the increasing number of patients move to the hospital in the middle of this other industrial competition hospitals that getting high. Research methods that were used with the quantitative approach, subject to a sample research that is 82 patients. Data were collected by means of instruments the questionnaire measured by scale Likert and in analysis with linear regression multiple with the result that the application of strategy differentiation having influence positive impact in creating customer loyalty in polyclinic MCU XYZ Cardiovascular Hospital, shown through value the regression coefficient ( b1 = 0,381 and t count = 4,444 with sig < 0,05.